2016
DOI: 10.17816/jowd65465-75
|View full text |Cite
|
Sign up to set email alerts
|

The role of bacterial biofilms in the development of chronic pathological processes in the vagina and endometrium

Abstract: Microbial biofilms are a problem in many areas of medicine. When the vaginal ecological system is disturbed, well-structured polymicrobial biofilm, covering the vaginal epithelium and consisting of anaerobic bacteria, is formed, which may lead to the development of recurrent bacterial vaginosis. During an ascending infection and the development of chronic endometritis, bacterial biofilms are detected in the endometrium. Biofilms formed by bacteria residing in the urogenital tract of woman, may result in dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…It was found that more often than other cervical mucus, which was taken for analysis in all subjects without exception, contained human papilloma virus, cytomegalovirus, fungal infection caused by Candida albicans, and mixed infection (viral and bacterial at the same time). Viral infection was prevalent in women with atypical forms of hyperplastic processes (Chaplin, Rebrikov, & Boldyreva, 2015;Pelzer et al, 2018;Podolskyi, Lisyana, & Ponomaryova, 2017;Shalepo, Mikhaylenko, & Savicheva, 2016), due to the strong correlation between viral tissue infection, primarily human papilloma virus, and the presence of genetically transformed cells, confirmed by a number of studies, including that indicating tissue changes in estrogen-sensitive areas caused by the papilloma virus. Candida albicans was a fairly frequent "companion" of chronic endometritis in the studied women, which can also contribute to the development of GPE, because, firstly, it develops by existing already reduced immunity, and secondly, suppresses cellular and humoral immunity; in ad-…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It was found that more often than other cervical mucus, which was taken for analysis in all subjects without exception, contained human papilloma virus, cytomegalovirus, fungal infection caused by Candida albicans, and mixed infection (viral and bacterial at the same time). Viral infection was prevalent in women with atypical forms of hyperplastic processes (Chaplin, Rebrikov, & Boldyreva, 2015;Pelzer et al, 2018;Podolskyi, Lisyana, & Ponomaryova, 2017;Shalepo, Mikhaylenko, & Savicheva, 2016), due to the strong correlation between viral tissue infection, primarily human papilloma virus, and the presence of genetically transformed cells, confirmed by a number of studies, including that indicating tissue changes in estrogen-sensitive areas caused by the papilloma virus. Candida albicans was a fairly frequent "companion" of chronic endometritis in the studied women, which can also contribute to the development of GPE, because, firstly, it develops by existing already reduced immunity, and secondly, suppresses cellular and humoral immunity; in ad-…”
Section: Resultsmentioning
confidence: 93%
“…It is believed that immune disorders, which can lead to endometrial hyperplasia, in more than 60% of cases are caused by viral and bacterial infectious agents (Haskhachih & Potapov, 2018;Sobczuk, Wrona, & Pertyński, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The microorganisms are catalase-and oxidase-negative; have a fermentative type of metabolism, inhibit H 2 O 2 , which is actively released by lactobacilli; hydrolyze starch, dextrin, maltose, ribose forming short chain volatile fatty acids with isomers (fractions C2-C6), mainly acetic C2. These compounds produce unpleasant smell of rotten fish [1,12] An influential factor in the pathogenicity of Gardnerella vaginalis is its adhesive ability, which enables bacteria to attach to the epithelium of the vaginal mucosa, colonize it and form a biofilm [15]. In experiments with the clinical material taken from 30 patients it has been shown that Gardnerella acts as the primary colonizer and probably contributes to the attachment of other opportunistic microorganisms [16].…”
Section: The Aimmentioning
confidence: 99%
“…The uterine cavity was regarded as sterile because cervical mucus, which has a high concentration of proinflammatory cytokines, immunoglobulins and antimicrobial peptides, provides a barrier effect [9]. Detection of microorganisms in the uterine cavity was associated with contamination of vaginal microflora samples, but high levels of colonization by endometrial microorganisms were detected in hysterectomy specimens in nonpregnant women [10, 12].…”
Section: Introductionmentioning
confidence: 99%
“…According to some scientists, the presence of a small number of bacteria in the uterine cavity cannot be considered a pathology [10, 14]. Pathological processes in the endometrium can occur if there is a high concentration of bacteria in the uterus, in the case of mixed bacterial microflora and the presence of virulent strains.…”
Section: Introductionmentioning
confidence: 99%